Conductive fiber bundle composite hydrogel material with three-level nested structure and preparation method thereof

The multi-step method of preparing composite conductive fiber materials with three-level nested structures has solved the processing problems of existing conductive polymer materials in spinal cord injury repair, poor biocompatibility and infection risk, and achieved the effects of high conductivity, antibacteriality and high biocompatibility.

CN116077727BActive Publication Date: 2025-03-18ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310039891.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-03-18
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

Existing conductive polymer materials have problems in processing, poor biocompatibility and prone to infection in the repair of spinal cord injury.

Method used

The sodium alginate/conductive polymer/polydopamine/nanosilver/polydopamine composite conductive fiber material with a tertiary nesting structure was prepared by multi-step method. The composite material with a multi-layer myelin structure was formed through processes such as sodium alginate fiber winding, conductive polymer in situ polymerization, dopamine self-polymerization, nanosilver redox and hydrogel outer membrane nesting.

Benefits of technology

The material is achieved with high conductivity, antibacteriality, high tensile strength and high biocompatibility, reducing the risk of infection and improving the effect of spinal cord injury repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116077727B_ABST
    Figure CN116077727B_ABST
Patent Text Reader

Abstract

The present invention discloses a conductive fiber bundle composite hydrogel material with a three-level nested structure and a preparation method thereof. The preparation method comprises: ① preparing a sodium alginate solution combined with wet spinning in a high Ca 2+ Preparation of sodium alginate fiber in a coagulation bath; ② Immersing the obtained fiber in a mixed aqueous solution of conductive polymer monomer / dopant for in-situ polymerization; ③ Immersing in dopamine / Tris buffer (pH=8.5) for in-situ self-polymerization; ④ Immersing the obtained sodium alginate / conductive polymer / polydopamine composite fiber in a silver nitrate solution under light-proof conditions for reaction to introduce a nanosilver coating; ⑤ Then a second dopamine in-situ polymerization is performed to obtain a composite conductive fiber with a multilayer myelin sheath structure; ⑥ Twisting and re-twisting the above fibers to obtain a composite fiber bundle, and nesting a gel outer membrane on the outside to obtain a conductive composite hydrogel material. This material has excellent biocompatibility, conductivity and anti-infection properties, and can be used in the field of spinal cord injury repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biomedical materials, and in particular to a conductive fiber bundle composite hydrogel material with a three-level nested structure and a preparation method thereof. Background Art

[0002] Spinal cord injury is the most serious complication of spinal cord injury, often leading to severe functional impairment of the limbs below the injured segment. Spinal cord injury not only causes serious physical and psychological harm to the patient, but also imposes a huge economic burden on the entire society. Due to the socioeconomic losses caused by spinal cord injury, the prevention, treatment and rehabilitation of spinal cord injury has become a major issue in today's medical community.

[0003] In recent years, with the rapid development of tissue engineering technology, various biomaterials for spinal cord injury repair have sprung up like mushrooms after a rain, and the conduction of electrical signals has shown a very unique role in promoting neuronal regeneration. Conductive polymers, as a new type of functional material, have been widely studied in the fields of spinal cord injury repair and nerve repair. However, on the one hand, natural spinal cord tissue has a certain spatial order in appearance structure and cell distribution, and there is electrical signal transmission between neurons. Simply filling with conductive polymer materials cannot achieve excellent repair effects; on the other hand, the biocompatibility of conductive polymers is general and the processability is poor.

[0004] Moreover, since conductive polymers are easily oxidized under high temperature conditions, they cannot be sterilized by high temperature and high pressure. Simple ultraviolet sterilization or 75% alcohol sterilization methods often make it easy to introduce bacteria during surgery when biomaterials are implanted for repair, causing infection at the surgical site.

[0005] Therefore, in view of the above background, the present invention prepares a biomaterial that can be used for spinal cord repair in the form of fibers. On the one hand, it overcomes the processing difficulties of conductive polymers, and on the other hand, it simulates the bionic three-dimensional structure of the spinal cord to smoothly restore the conduction of spinal nerve electrical signals. At the same time, dopamine and nanosilver are introduced in the form of a multilayer structure to solve the problems of biocompatibility and infection. Summary of the invention

[0006] The purpose of the present invention is to provide a conductive fiber bundle composite hydrogel material with a three-level nested structure and a preparation method thereof, in response to the clinical problems of nerve and spinal cord injuries. The material is expected to be used for spinal cord injury repair while solving the accompanying tissue infection problem.

[0007] The present invention is implemented by the following technical solutions:

[0008] The material is a conductive fiber bundle composite hydrogel material with a three-level nested structure. The specific preparation steps are as follows:

[0009] 1) Prepare sodium alginate into a solution of a certain concentration and inject it into a high concentration Ca 2+ in a coagulation bath and collected by a fiber winding collection device;

[0010] 2) The sodium alginate fibers on the winding collection device in step 1) (without removing free calcium ions to ensure that the fibers will not degrade during the polymerization process) are transferred to a rotating device (the above-mentioned fiber monolayer can be orderly wound on the rotating device), and the device is immersed in a conductive polymer monomer / dopant composite aqueous solution for a certain period of time, and an initiator is added to initiate the in-situ polymerization of the conductive polymer monomer on the fiber surface to obtain sodium alginate /

[0011] Conductive polymer composite fibers, after the reaction is completed, use deionized dialysis to remove monomers and other impurities;

[0012] 3) immersing the composite fiber obtained in step 2) together with the rotating device in dopamine / Tris buffer (pH=8.5) for in-situ self-polymerization to obtain sodium alginate / conductive polymer / polydopamine composite fiber, and dialyzing with deionized water;

[0013] 4) Under light-proof conditions, immersing the composite fiber in step 3) together with the rotating device in a silver nitrate solution, obtaining a nanosilver coating on the fiber surface through the reduction of polydopamine, and dialyzing with deionized water;

[0014] 5) immersing the composite fiber obtained in step 4) together with the rotating device in a dopamine / Tris buffer (pH=8.5) for secondary in-situ self-polymerization, and after post-treatment steps such as rinsing and drying, finally obtaining a sodium alginate / conductive polymer / polydopamine / nanosilver / polydopamine composite conductive fiber material with a multilayer myelin structure;

[0015] 6) After the above-mentioned composite conductive fibers are twisted into bundles, they are nested in the center of a transparent cylindrical mold, the upper and lower ends are fixed (to ensure that the fiber bundles do not fall apart), the lower end is sealed, and the hydrogel pre-solution is injected from the upper end to allow the solution to be in situ cured / photocured to obtain a composite conductive fiber bundle material nested with a hydrogel outer membrane.

[0016] Furthermore, in step 1), the viscosity of sodium alginate (10 g / L, 20° C.) is 0.02-0.1 Pa·s, and the concentration of the sodium alginate solution is 2-6 wt %; the calcium ion coagulation bath comprises 5-20 wt % calcium chloride, 0.5-3 wt % sodium sulfate, and 0.5-3 wt % sodium acetate, and the solvent system is a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water can be one of 70:30, 60:40, 50:50, 40:60, 30:70, etc.; the injection rate of the microinjection pump is 5-15 ml / min, and the injection aperture is 150-500 microns; the rotation speed of the collecting device is 50-150 rpm;

[0017] Furthermore, the conductive polymer monomer in step 2) is one or more of aniline, pyrrole, thiophene and their derivatives, with a concentration of 0.01-0.1wt%; the dopant includes phytic acid, hydrochloric acid, etc., with a concentration of 5-10wt%; the initiator includes one or more of ammonium persulfate, sodium persulfate, potassium persulfate, etc., with an amount of 0.5-1.5wt%; the immersion time is 0.5-4 hours; the rotation speed of the rotating device is 30-60 rpm; the polymerization time is 4-8h;

[0018] Furthermore, in step 3) and step 5), the dopamine concentration is 2-8 mg / ml, the reaction time is 8-72 hours, and the rotation speed of the rotating device is 30-60 rpm;

[0019] Furthermore, in step 4), the concentration of silver nitrate is 0.10-0.30 mol / L, the reaction time is 8-72 hours, and the rotation speed of the rotating device is 30-60 rpm;

[0020] Furthermore, the composite conductive fibers in the step 6) are generally twisted into bundles of 2-4 fibers, and then the 2-4 fiber bundles are twisted again to obtain the desired composite fiber bundles; the hydrogel pre-solution is one or more of GelMA, ChiMA, AlgMA, oxidized hyaluronic acid / Gelatin, etc., wherein the oxidized hyaluronic acid / Gelatin is gelled in situ by Schiff base reaction, and GelMA, ChiMA, AlgMA, HAMA, etc. are gelled by in situ photocuring, and the polymer concentration is 5-20wt%. If photoinitiation is required, the photoinitiator is one or more of LAP, IC-2959 and VA086, etc., the initiator concentration is 0.01-0.05wt%, and the photocuring time is 2-60 minutes.

[0021] Compared with the prior art, the present invention has the following advantages / innovations:

[0022] 1) Through a multi-step method (wet spinning + in-situ free radical polymerization + self-polymerization + redox reaction + self-polymerization + in-situ gelation nesting), sodium alginate, calcium salt, conductive polymer monomer, dopant, dopamine, silver nitrate, etc. are used as raw materials to prepare a sodium alginate / conductive polymer / polydopamine / nanosilver / polydopamine composite conductive fiber material (primary structure) with a multilayer myelin structure, and then the above fibers are twisted and re-twisted to obtain a composite fiber bundle (secondary structure) with an axial spiral arrangement structure, and then the in-situ gelation process is further combined to nest the hydrogel outer membrane on the outside of the fiber bundle, and the "secondary structure" is wrapped and fixed to form a "tertiary structure". The material also has conductive properties, antibacterial properties, high tensile strength, high biocompatibility, and biodegradability. The present invention achieves innovation in raw materials, processes and structures;

[0023] 2) In the present invention, organic synergistic enhancement of various raw material properties is achieved through raw material selection, preparation process regulation, and structural design: high molecular weight sodium alginate and high concentration calcium ion coagulation bath, multi-layer composite structure (microscopic multiple network structure and macroscopic multi-layer myelin sheath structure) and the final drying process (drawing effect on the fiber during the drying process) are selected to give the fiber high tensile strength; the combination of conductive polymer and dopant realizes high conductivity of the fiber; double-layer dopamine realizes the synthesis (reduction) and stabilization of nanosilver, the first layer of polydopamine serves as the site for the formation of nanosilver, and the second layer of polydopamine wraps the nanosilver, delays the release of nanosilver, reduces its toxicity, and improves the biocompatibility of the material; the outermost gel membrane uses GelMA and other materials with high biocompatibility, degradability, photocuring or self-crosslinking functions to fix the structure of the fiber bundle in situ;

[0024] 3) After the composite conductive fiber material is implanted in the body, the axially arranged conductive polymer fiber bundles can realize the bionic simulation of the spinal cord structure. The directional conduction of electrical stimulation can be achieved through an external power supply or by utilizing the biological body's own bioelectric signals, thereby repairing spinal cord injuries and solving the accompanying infection problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of a composite conductive fiber structure with a multi-layer myelin sheath structure;

[0026] Figure 2 A schematic diagram of forming a composite fiber bundle by twisting and re-twisting a composite conductive fiber with a multi-layer myelin structure;

[0027] Figure 3 Schematic diagram of the structure of the spinal cord injury repair material consisting of a composite conductive fiber bundle nested in a gel outer membrane. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific examples.

[0029] Embodiment 1:

[0030] 1) Prepare 4 wt% sodium alginate solution and inject it into the Ca 2+ The solidified material was placed in a coagulation bath (a mixed solution of 10 wt % calcium chloride, 0.5 wt % sodium sulfate, 0.5 wt % sodium acetate, ethanol: water = 50:50 (v:v)) and collected by a fiber winding collection device (collection rate was 50 rpm);

[0031] 2) transferring the sodium alginate fiber (without removing free calcium ions) on the winding collection device in step 1) to a rotating device, and immersing the device together with the fiber in an aniline / phytic acid composite aqueous solution (0.05wt% / 5wt%) for 30 minutes at a rotation rate of 30 rpm, adding an ammonium persulfate initiator (0.5wt%) to initiate in-situ polymerization of aniline on the fiber surface for 4 hours to obtain a sodium alginate / conductive polymer composite fiber, and after the reaction, using deionized water for dialysis to remove monomers and other impurities;

[0032] 3) immersing the composite fiber obtained in step 2) together with the rotating device in 2 mg / ml dopamine / Tris buffer (pH=8.5) for in-situ self-polymerization for 12 hours at a rotation speed of 30 rpm to obtain sodium alginate / conductive polymer / polydopamine composite fiber, and dialyzing with deionized water;

[0033] 4) Under light-proof conditions, immersing the composite fiber in step 3) together with the rotating device in a silver nitrate solution (0.10 mol / L), reacting for 8 hours at a rotation rate of 30 rpm, obtaining a nanosilver coating on the fiber surface through the reduction of polydopamine, and dialyzing with deionized water;

[0034] 5) immersing the composite fiber obtained in step 4) together with the rotating device in 2 mg / ml dopamine / Tris buffer (pH=8.5) for secondary in-situ self-polymerization for 12 hours, and after post-treatment steps such as rinsing and low-temperature drying at 37°C, finally obtaining a sodium alginate / polyaniline / polydopamine / nanosilver / polydopamine composite conductive fiber material with a multilayer myelin structure;

[0035] 6) After twisting the above four composite conductive fibers into a fiber bundle, the four fiber bundles are twisted again to form a composite fiber bundle, which is nested in the center of a transparent cylindrical mold. The upper and lower ends are fixed with clamps (to ensure that the composite fiber bundle does not fall apart), the lower end is sealed, and the GelMA / LAP hydrogel pre-solution (PBS solvent, concentration of 10wt% / 0.25wt%) is injected from the upper end. The solution is in situ cured / photocured for 5 minutes, and the mold is removed to obtain a composite conductive fiber bundle material nested with a hydrogel outer membrane.

[0036] 7) The diameter of the conductive fiber with a multi-layer myelin structure is 126.4 microns, the conductivity of the hydrogel material is 3.1S / cm, the survival rate of the material extract CCK-8 result is 96.3%, the silver release concentration in 24 hours is 0.421 mg / mL, the material has a significant antibacterial zone effect, and degrades by 56.1% in 28 days.

[0037] Embodiment 2:

[0038] 1) Prepare 4 wt% sodium alginate solution and inject it into the Ca 2+ The solidified material was placed in a coagulation bath (a mixed solution of 10 wt% calcium chloride, 0.5 wt% sodium sulfate, 0.5 wt% sodium acetate, ethanol: water = 50:50) and collected by a fiber winding collection device (collection rate was 50 rpm);

[0039] 2) transferring the sodium alginate fiber (without removing free calcium ions) on the winding collection device in step 1) to a rotating device, and immersing the device together with the fiber in an aniline / phytic acid composite aqueous solution (0.10wt% / 7.5wt%) for 30 minutes at a rotation rate of 30 revolutions per minute, adding an ammonium persulfate initiator (0.75wt%) to initiate in-situ polymerization of aniline on the fiber surface for 8 hours to obtain a sodium alginate / conductive polymer composite fiber, and after the reaction, using deionized water for dialysis to remove monomers and other impurities;

[0040] 3) immersing the composite fiber obtained in step 2) together with the rotating device in 2 mg / ml dopamine / Tris buffer (pH=8.5) for in-situ self-polymerization for 12 hours at a rotation speed of 30 rpm to obtain sodium alginate / conductive polymer / polydopamine composite fiber, and dialyzing with deionized water;

[0041] 4) Under light-proof conditions, immersing the composite fiber in step 3) together with the rotating device in a silver nitrate solution (0.10 mol / L), reacting for 8 hours at a rotation rate of 30 rpm, obtaining a nanosilver coating on the fiber surface through the reduction of polydopamine, and dialyzing with deionized water;

[0042] 5) immersing the composite fiber obtained in step 4) together with the rotating device in 2 mg / ml dopamine / Tris buffer (pH=8.5) for secondary in-situ self-polymerization for 12 hours, and after post-treatment steps such as rinsing and low-temperature drying at 37°C, finally obtaining a sodium alginate / polyaniline / polydopamine / nanosilver / polydopamine composite conductive fiber material with a multilayer myelin structure;

[0043] 6) After twisting the above four composite conductive fibers into a fiber bundle, the four fiber bundles are twisted again to form a composite fiber bundle, which is nested in the center of a transparent cylindrical mold. The upper and lower ends are fixed with clamps (to ensure that the composite fiber bundle does not fall apart), the lower end is sealed, and the GelMA / LAP hydrogel pre-solution (PBS solvent, concentration of 10wt% / 0.25wt%) is injected from the upper end. The solution is in situ cured / photocured for 5 minutes, and the mold is removed to obtain a composite conductive fiber bundle material nested with a hydrogel outer membrane.

[0044] 7) Compared with Example 1, the aniline concentration was increased, the polymerization time was increased, the diameter of the conductive fiber with a multilayer myelin structure was 131.6 microns, the conductivity of the hydrogel material was 4.2S / cm, the survival rate of the material extract CCK-8 result was 94.1%, the silver release concentration in 24 hours was 0.452 mg / mL, the material had an obvious antibacterial zone effect, and degraded 49.5% in 28 days.

[0045] Embodiment 3:

[0046] 1) Prepare 6 wt% sodium alginate solution and inject it into the Ca 2+ The solidified material was placed in a coagulation bath (a mixed solution of 20 wt % calcium chloride, 1.0 wt % sodium sulfate, 1.0 wt % sodium acetate, ethanol: water = 30:70 (v:v)) and collected by a fiber winding collection device (collection rate was 50 rpm);

[0047] 2) transferring the sodium alginate fiber (without removing free calcium ions) on the winding collection device in step 1) to a rotating device, and immersing the device together with the fiber in an aniline / phytic acid composite aqueous solution (0.05wt% / 5wt%) for 30 minutes at a rotation rate of 30 rpm, adding an ammonium persulfate initiator (0.5wt%) to initiate in-situ polymerization of aniline on the fiber surface for 4 hours to obtain a sodium alginate / conductive polymer composite fiber, and after the reaction, using deionized water for dialysis to remove monomers and other impurities;

[0048] 3) immersing the composite fiber obtained in step 2) together with the rotating device in 2 mg / ml dopamine / Tris buffer (pH=8.5) for in-situ self-polymerization for 12 hours at a rotation speed of 30 rpm to obtain sodium alginate / conductive polymer / polydopamine composite fiber, and dialyzing with deionized water;

[0049] 4) Under light-proof conditions, immersing the composite fiber in step 3) together with the rotating device in a silver nitrate solution (0.10 mol / L), reacting for 8 hours at a rotation rate of 30 rpm, obtaining a nanosilver coating on the fiber surface through the reduction of polydopamine, and dialyzing with deionized water;

[0050] 5) immersing the composite fiber obtained in step 4) together with the rotating device in 2 mg / ml dopamine / Tris buffer (pH=8.5) for secondary in-situ self-polymerization for 12 hours, and after post-treatment steps such as rinsing and low-temperature drying at 37°C, finally obtaining a sodium alginate / polyaniline / polydopamine / nanosilver / polydopamine composite conductive fiber material with a multilayer myelin structure;

[0051] 6) After twisting the above four composite conductive fibers into a fiber bundle, the four fiber bundles are twisted again to form a composite fiber bundle, which is nested in the center of a transparent cylindrical mold. The upper and lower ends are fixed with clamps (to ensure that the composite fiber bundle does not fall apart), the lower end is sealed, and the GelMA / LAP hydrogel pre-solution (PBS solvent, concentration of 10wt% / 0.25wt%) is injected from the upper end. The solution is in situ cured / photocured for 5 minutes to obtain a composite conductive fiber bundle material nested with a hydrogel outer membrane.

[0052] 7) Compared with Example 1, the concentration of sodium alginate is increased, and the Ca 2+ As the concentration increased, the spinning hole diameter increased, and the diameter of the conductive fiber with a multi-layer myelin structure was 241.3 microns. The conductivity of the hydrogel material was 2.4S / cm, the survival rate of the material extract CCK-8 was 95.4%, the silver release concentration in 24 hours was 0.538 mg / mL, the material had a significant antibacterial zone effect, and degraded by 62.4% in 28 days.

[0053] Embodiment 4:

[0054] 1) Prepare 4 wt% sodium alginate solution and inject it into the Ca 2+ The solidified material was placed in a coagulation bath (a mixed solution of 10 wt % calcium chloride, 0.5 wt % sodium sulfate, 0.5 wt % sodium acetate, ethanol: water = 50:50 (v:v)) and collected by a fiber winding collection device (collection rate was 50 rpm);

[0055] 2) transferring the sodium alginate fiber (without removing free calcium ions) on the winding collection device in step 1) to a rotating device, and immersing the device together with the fiber in an aniline / phytic acid composite aqueous solution (0.05wt% / 5wt%) for 30 minutes at a rotation rate of 30 rpm, adding an ammonium persulfate initiator (0.5wt%) to initiate in-situ polymerization of aniline on the fiber surface for 4 hours to obtain a sodium alginate / conductive polymer composite fiber, and after the reaction, using deionized water for dialysis to remove monomers and other impurities;

[0056] 3) immersing the composite fiber obtained in step 2) together with the rotating device in 4 mg / ml dopamine / Tris buffer (pH=8.5) for in-situ self-polymerization for 48 hours at a rotating speed of 30 rpm to obtain a sodium alginate / conductive polymer / polydopamine composite fiber, and dialyzing with deionized water;

[0057] 4) Under light-proof conditions, immersing the composite fiber in step 3) together with the rotating device in a silver nitrate solution (0.10 mol / L), reacting for 8 hours at a rotation rate of 30 rpm, obtaining a nanosilver coating on the fiber surface through the reduction of polydopamine, and dialyzing with deionized water;

[0058] 5) immersing the composite fiber obtained in step 4) together with the rotating device in 4 mg / ml dopamine / Tris buffer (pH=8.5) for secondary in-situ self-polymerization for 48 hours, and after post-treatment steps such as rinsing and low-temperature drying at 37°C, finally obtaining a sodium alginate / polyaniline / polydopamine / nanosilver / polydopamine composite conductive fiber material with a multilayer myelin structure;

[0059] 6) After twisting the above four composite conductive fibers into a fiber bundle, the four fiber bundles are twisted again to form a composite fiber bundle, which is nested in the center of a transparent cylindrical mold. The upper and lower ends are fixed with clamps (to ensure that the composite fiber bundle does not fall apart), the lower end is sealed, and the GelMA / LAP hydrogel pre-solution (PBS solvent, concentration of 10wt% / 0.25wt%) is injected from the upper end. The solution is in situ cured / photocured for 5 minutes, and the mold is removed to obtain a composite conductive fiber bundle material nested with a hydrogel outer membrane.

[0060] 7) Compared with Example 1, the dopamine concentration is increased, the polymerization time is prolonged, the diameter of the conductive fiber with a multilayer myelin structure is 131.2 microns, the conductivity of the hydrogel material is 2.74S / cm, the survival rate of the material extract CCK-8 result is 97.4%, the silver release concentration in 24 hours is 0.449 mg / mL, the material has an obvious antibacterial zone effect, and degrades 54.7% in 28 days.

Claims

1. A conductive fiber bundle composite hydrogel material with a three-level nested structure, characterized in that: The composite hydrogel material is a composite conductive fiber with a multi-layer myelin structure as a primary structure, a composite fiber bundle secondary structure is obtained by twisting and re-twisting, and a gel outer membrane is nested on the outside to obtain a conductive fiber bundle composite hydrogel material with a tertiary nested structure; the composite conductive fiber with a multi-layer myelin structure is firstly prepared by using a sodium alginate solution in combination with a wet spinning process to prepare a sodium alginate fiber, and then using an in-situ free radical polymerization process to prepare a sodium alginate / conductive polymer composite fiber, and then using a dopamine-Tris buffer solution to introduce a polydopamine layer, and using the reduction effect of polydopamine on silver nitrate to introduce a nanosilver layer, and finally introducing a polydopamine layer for a second time to obtain the composite conductive fiber.

2. The conductive fiber bundle composite hydrogel material with a three-level nested structure as claimed in claim 1, characterized in that: The preparation method thereof comprises the following steps: 1) Prepare sodium alginate solution and inject it into the high concentration Ca using a microinjection pump. 2+ in a coagulation bath and collected by a fiber winding collection device; 2) directly transferring the sodium alginate fibers on the winding collection device in step 1) to a rotating device, and immersing them together in a conductive polymer monomer / dopant composite aqueous solution, adding an initiator to initiate in-situ polymerization of the conductive polymer monomer on the fiber surface to obtain a sodium alginate / conductive polymer composite fiber, and using deionized dialysis to remove impurities after the reaction is completed; 3) immersing the composite fiber obtained in step 2) together with the rotating device in dopamine / Tris buffer (pH=8.5) for in-situ self-polymerization to obtain sodium alginate / conductive polymer / polydopamine composite fiber, and dialyzing with deionized water; 4) Under light-proof conditions, immersing the composite fiber obtained in step 3) together with the rotating device in a silver nitrate solution, obtaining a nanosilver coating on the fiber surface through the reduction of polydopamine, and dialyzing with deionized water; 5) immersing the composite fiber obtained in step 4) together with the rotating device in a dopamine / Tris buffer (pH=8.5) for secondary in-situ self-polymerization, and after rinsing and drying, obtaining a sodium alginate / conductive polymer / polydopamine / nanosilver / polydopamine composite conductive fiber material with a multilayer myelin structure; 6) After twisting the above-mentioned composite conductive fibers into bundles, they are nested in the center of a transparent cylindrical mold, the upper and lower ends are fixed to ensure that the fiber bundles do not fall apart, one end is sealed, and the hydrogel pre-solution is injected from the other end to solidify the solution, thereby nesting the hydrogel outer film on the surface of the composite conductive fibers, and removing the mold to obtain a conductive fiber bundle composite hydrogel material with a three-level nested structure.

3. The conductive fiber bundle composite hydrogel material with a three-level nested structure as claimed in claim 2, characterized in that: In step 1), at 20° C., the viscosity of 10 g / L sodium alginate is 0.02-0.1 Pa·s, and the concentration of the sodium alginate solution is 2-6 wt %; the calcium ion coagulation bath comprises 5-20 wt % calcium chloride, 0.5-3 wt % sodium sulfate, and 0.5-3 wt % sodium acetate, and the solvent system is a mixed solution of ethanol and water; the injection rate of the microinjection pump is 5-15 ml / min, and the injection aperture is 150-500 microns; and the rotation speed of the collecting device is 50-150 rpm.

4. The conductive fiber bundle composite hydrogel material with a three-level nested structure as claimed in claim 2, characterized in that: The conductive polymer monomer in step 2) is one or more of aniline, pyrrole, thiophene and their derivatives, with a concentration of 0.01-0.1wt%; the dopant is one or more of phytic acid and hydrochloric acid, with a concentration of 5-10wt%; the initiator is one or more of ammonium persulfate, sodium persulfate and potassium persulfate, with an amount of 0.5-1.5wt%; the immersion time is 0.5-4 hours; the rotation speed of the rotating device is 30-60 rpm; and the polymerization time is 4-8 hours.

5. The conductive fiber bundle composite hydrogel material with a three-level nested structure as claimed in claim 2, characterized in that: In step 3) and step 5), the dopamine concentration in the dopamine / Tris buffer is 2-8 mg / ml, the reaction time is 8-72 hours, and the rotation speed of the rotating device is 30-60 rpm.

6. The conductive fiber bundle composite hydrogel material with a three-level nested structure as claimed in claim 2, characterized in that: In step 4), the concentration of the silver nitrate solution is 0.10-0.30 mol / L, the reaction time is 8-72 hours, and the rotation speed of the rotating device is 30-60 rpm.

7. The conductive fiber bundle composite hydrogel material with a three-level nested structure as claimed in claim 2, characterized in that: In step 6), 2-4 composite conductive fibers are twisted into bundles, and then the 2-4 fiber bundles are twisted again to obtain a composite fiber bundle; the hydrogel pre-solution is one or more of GelMA, AlgMA, HAMA, and oxidized hyaluronic acid / Gelatin, wherein the oxidized hyaluronic acid / Gelatin is in situ gelled by Schiff base reaction, and GelMA, AlgMA, and HAMA are gelled by in situ photocuring.

Citation Information

Patent Citations

  • Oriented conductive collagen hydrogel, biomimetic conductive nerve scaffold material and preparation method of oriented conductive collagen hydrogel and biomimetic conductive nerve scaffold material

    CN110124113A

  • Single-walled carbon nanotube composite material conductive nerve cannula and preparation method and application thereof

    CN111001036A